Vegetable growing of open ground in the south of Russia. State and development trends - R. A. Gish (Овощи России)
Relevance. The south of Russia occupies about 45% of the country's vegetable area and produces annually more than 5.7 million tons of vegetables or 48.9% of gross vegetable harvest in the country. The analysis of the state of open-ground vegetable growing in the south of Russia is given, taking into account the dynamics of acreage, yield, and gross harvest. The article presents a forecast of the development of openground vegetable growing in the south of Russia in the medium term, taking into account the organizational and legal changes in the industry.Materials and results. The purpose of the research. Analysis of the state of open-ground vegetable growing in the south of Russia and identification of factors hindering the further development of the industry. The role of innovations introduced into production, variety exchange and variety renewal in increasing the gross yield of vegetables are shown. The reasons of the shortfall in productivity in 10 of 15 subjects of districts below the level of the average district values are given. The article highlights the reasoned judgments about the need to enlarge vegetable farms, expand the range of vegetable crops grown, as well as the need for a widespread transition to organic vegetable growing. The paper uses the official materials of the Federal State Statistics Service (FSSS), reports of agricultural departments of the subjects of two districts, the analysis of which was carried out by the author and comments on them were made.